The student centered education and knowledge economy - Canlı, Gamze. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
This thesis investigates the implications and assumptions of the student-centered education model, which was embarked at the primary school level in 2005. The reforms and policies regarding the education models attempt to cultivate a specific model of self as the educated subject, which is envisioned as to contribute to the socio-economic development being adapted and productive. This thesis aims at analyzing the student centered education model from such a view point, acknowledging that it promotes an ideal image of self. It asks the questions what the idealized qualities of self are; who the educated subject is; how these correlate with the current political economy settlement; and, what kind of a rationality of government do all of these establish. Through these questions, it targets to investigate the correlations of the idealized subjectivity in the student-centered education model with the assumptions and requirements of knowledge economy and the neoliberal regime of government. In this framework, the promoted skills and attainments of learners in the curriculum are scrutinized and they are compared with the idealized qualities of a knowledge economy worker which are mentioned in the international sources. Here, the importance and implications of the abilities such as problem solving, learning to learn, creativity, flexibility, entrepreneurship, and communication are discussed. It is also argued that the qualities of self responsibility, self actualization and self consciousness are promoted in the student centered education as the underlying features of subjectivity and government of self. In this respect, this thesis makes the claim that student-centered education model expects to produce self-governing individuals, attempting to establish the neoliberal regime of government in schools. From a more general aspect, this pedagogical arrangement targets to produce ideal subjects for the development and well-functioning of knowledge economy; and, for this purpose, it employs the neoliberal regime of government.
Keywords: Student-centered learning -- Turkey.; Knowledge economy -- Turkey.